A formação docente nos documentos da ANFOPE, nas DCNS e na pedagogia - Fontanella, Silvane (2011)
This work, included in the line of educational policy research, has the theme as a guiding teacher training. The main goal is the relentless search for the identity of the teacher after the imposition of national curricular guidelines for the Education Faculty. For that we use as a methodological document analysis, the final documents of the national meetings of the National Association for the Education of Professional Educators, highlighting the systematic and historic three categories: teacher training, pedagogy course and common national base. Later, in his own DCNs and in some documents before and after its publication, identify the similarities and differences between Anfope DCNs and the pedagogy course. We finished the survey with an analysis of the main sources of literature on the subject in order to show the importance of training consistently, further study by the continuing education and the challenges the teacher faces in the world of work, always using as base the comparative DCNs and documents of Anfope